2008
DOI: 10.2147/vhrm.s1653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of statins in managing cardiovascular risk

Abstract: Abstract:Since their introduction in the 1980s, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) have emerged as the one of the best-selling medication classes to date, with numerous trials demonstrating powerful effi cacy in preventing cardiovascular outcomes. As our understanding of low-density lipoprotein cholesterol (LDL-C) and atherosclerosis continues to grow, the concept of 'lower is better' has corresponded with a 'more is better' approach to statin-based therapy. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 76 publications
2
94
0
3
Order By: Relevance
“…The results obtained from the study revealed that all the brands passed the general standard specifications for dissolution rate test for conventional release tablets. The difference in the result can be correlated to all factors which affect the dissolution rate from the raw material (purity) which can affect solubility, and all diluents which were used in the formulation of each brand [27][28][29][30] . The results obtained from the assessment of the percentage content of active ingredient in the four brands showed that all brands gave values within the specification which is average weight content between 95-105% of Simvastatin 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from the study revealed that all the brands passed the general standard specifications for dissolution rate test for conventional release tablets. The difference in the result can be correlated to all factors which affect the dissolution rate from the raw material (purity) which can affect solubility, and all diluents which were used in the formulation of each brand [27][28][29][30] . The results obtained from the assessment of the percentage content of active ingredient in the four brands showed that all brands gave values within the specification which is average weight content between 95-105% of Simvastatin 31 .…”
Section: Resultsmentioning
confidence: 99%
“…We did not consider treatment with nonstatin, lipid-lowering medications in our eligibility stratification as such individuals may still be candidates for additional statin therapy. 27 Subjects were deemed to be at the highest risk level if they had CHD or a CHD risk equivalent, which included diabetes, peripheral artery disease, symptomatic carotid artery disease, or abdominal aortic aneurysm. CHD was assessed through self-report of coronary artery disease, myocardial infarction, or angina pectoris.…”
Section: Ncep/atpiii-indicated Groupmentioning
confidence: 99%
“…Inhibiting LVH has emerged as a primary target for therapeutic approaches in preventing hypertension-induced end-organ damage [35]. Statins, hydroxymethylglutaryl-coenzyme A reductase inhibitors, are widely prescribed cholesterol-lowering agents that decrease the incidence of myocardial infarction and ischaemic stroke [26]. Simvastatin (SIM), a member of statins, has been recognised to have antioxidant effects and is an effective agent for preventing the development of cardiac hypertrophy (through an antioxidant mechanism) [51].…”
Section: Introductionmentioning
confidence: 99%